Penentuan HLB Butuh Suatu Bahan Dengan Sistem HLB - Rofienda Rofienda (Balai Besar Kimia dan Kemasan, 1989)
HLB-system is a method to determine the required HLB of a substance by using aset of standard emulsifiers with certain HLB values as and aid.Experiment has been carried out to determine the required HLB in emulsion making of BPMC in Xylol.The result indicates that the stabiiity of this emulsion has been achieved in sixty minutes at the HLB value of 12.